Optimization of Pharmacotherapy with Direct Oral Anticoagulants: the Need to Choose the Right Dosage Regimen - A. I. Kochetkov; O. D. Ostroumova (Столичная издательская компания, 2019)
In recent years, there has been a persistent trend towards the more frequent prescription of direct oral anticoagulants (DOACs) compared with vitamin K antagonists due to the extensive body of evidence showing their high safety and efficacy, which in some cases exceed those of warfarin, and also by reason of there is no necessity for regular monitoring of international normalized ratio. However, the question of the reasonable and rational prescription of DOACs becomes relevant, including issues of their dosing, especially as a result of increasing in the number of patients with a complex cardiovascular risk profile and multimorbidity. In these terms, apixaban stands high among the DOAC class, and its high efficacy and safety both in full dose and reasonably reduced dosage has been proved, including older patients, patients with chronic kidney disease, coronary artery disease, with history of acute coronary syndrome and individuals undergoing percutaneous coronary intervention. This DOAC has strict indications to reduce the dose, they are specified in the drug label, and in such cases a reduced dose should be prescribed, in these clinical conditions the effectiveness and safety of apixaban is also proven. The favorable apixaban pharmacokinetic properties, consisting in low renal clearance, lack of clinically relevant interaction with food and the linear smooth effect on the blood coagulation components without episodes of hypo- and hypercoagulation, are the most important components of high efficacy and safety of this DOAC. The optimal efficacy and safety coupling of apixaban is reflected in the exclusively high patients' adherence to the treatment confirmed by evidence-based medicine data, and therefore there is no necessity for additional procedures to maintain adherence. All the aforementioned facts allow us to recommend apixaban for widespread use in patients requiring anticoagulant therapy for optimal prevention of systemic thromboembolism and minimizing the associated risk of bleeding.